A first study of the complex-concentrated-alloy W38Ta36Cr15V11 in Pisces-RF high-flux deuterium plasma - M.T. Vigil; S. Faulhaber; M.I. Patino; A. Založnik; D. Nishijima; M.J. Simmonds; B. Schwendeman; K. Vecchio; G.R. Tynan; M.J. Baldwin (Nuclear Materials and Energy)
Bulk targets of W38Ta36Cr15V11 complex concentrated alloy (CCA) were produced by spark plasma sintering at the Vecchio materials research lab at the University of California–San Diego. Targets fabricated were reasonably dense, BCC phase, compositionally close in match to that of El-Atwani et al. (2019), and homogeneous, as measured by electron microscopy, energy dispersive x-ray microanalysis (EDX), EDX mapping, and x-ray diffraction. The targets were exposed to deuterium plasma of associated 100 eV ion fluences of 2×1026 m−2 at 523 K, 773 K and 1023 K in the Pisces-RF high-flux linear plasma device. Plasma exposure is found to produce surface compositional enrichment in W and Ta, as determined by Auger electron spectroscopy and EDX, that is caused by a depletion of surface Cr and V, the former being observed with optical emission spectroscopy in the target plasma. Accompanying the compositional change, transient grating spectroscopy analysis, taken pre- and post-plasma exposure on the 1023 K exposed target, revealed ∼30% reduction in surface thermal diffusivity from 9.4×10−6 m2s−1 to 6.7×10−6 m2s−1. Lastly, D retention in the CCA targets was found to be characterized by a singular thermal release peak at ∼900 K, and retention varied from 2×1023 m−2 to 3×1020 m−2 for exposure in the temperature range 523–1023 K, as measured by thermal desorption spectrometry. This level of D retention is found to be high relative to pure tungsten.